2023
DOI: 10.1002/acr.25054
|View full text |Cite
|
Sign up to set email alerts
|

A Provider‐Based Approach to Address Racial Disparities in Lupus Clinical Trial Participation

Abstract: Objective Substantial disparities exist in clinical trial participation, which is problematic in diseases such as lupus that disproportionately affect racial/ethnic minority populations. Our objective was to examine the effectiveness of an online educational course aiming to train medical providers to refer Black and Latino patients to lupus clinical trials (LCTs). Methods The American College of Rheumatology's Materials to Increase Minority Involvement in Clinical Trials (MIMICT) study used an online, randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Black Americans are far less likely to enroll in research trials than would be expected based on disease prevalence [10]. Although better framing of randomized controlled trials and medical professional training may help [11,12], the distrust of research may be well justified. Recent papers have suggested that Black and White research participants are treated differently within the same trials [13].…”
Section: Research Participationmentioning
confidence: 99%
“…Black Americans are far less likely to enroll in research trials than would be expected based on disease prevalence [10]. Although better framing of randomized controlled trials and medical professional training may help [11,12], the distrust of research may be well justified. Recent papers have suggested that Black and White research participants are treated differently within the same trials [13].…”
Section: Research Participationmentioning
confidence: 99%
“…Data from a recent review propose that the barriers to new treatments in SLE include patient factors, provider factors, and system factors (15). Improving patientprovider communication and shared decision making is likely to result in increased participation in clinical trials (16,17).…”
Section: Introductionmentioning
confidence: 99%